Pastoral & teaching comments on “Caritas in Veritate” by Benedicto XVI - Osorio Torres, Juan Alberto (2010)
Caritas in Veritate (2009) is the first encyclical letter of Pope Benedict XVI, dedicated specifically to the Social Doctrine of the Church, after having written two others, from the beginning of his pope, Deus Caritas Est (2006) and Spes Salvi(2007). To prepare this article, it was necessary to revise the text  Jesus of Nazareth (2007), the first volume published by the Theologian Pope, so to capture the unity and coherence of his thought. Because, in the second part of Deu scaritas est, before listing the social encyclical letters from Rerum Novarum to Centesimus Annus and from this to the publication of Compendium of the Church’s Social Doctrine, the Pope speaks of charity as the responsibility of the church, he dedicates a special section to justice and politics, and makes important remarks about the relations hip between justice and charity, issues that should be considered in teaching and pastoral care.